2018
DOI: 10.1615/plasmamed.2018023695
|View full text |Cite
|
Sign up to set email alerts
|

Excitation Wavelength and Temperature at Irradiation of Metal by Atmospheric-Pressure Nonequilibrium Argon Plasma

Abstract: We studied excitation wavelength and temperature during irradiation of atmospheric-pressure nonequilibrium argon plasma to pure metal plate. We observed excitation emission of light activated by argon plasma in the same wavelength region, both with and without metal plate. The wavelength region activated by atmospheric-pressure nonequilibrium argon plasma was limited. In the presence of the ion corresponding to wavelength region activated by argon plasma, corresponding ions were activated. Both oxygen ions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Besides, we also reported that the absolute density of Ar(1s5) metastables depends on the permittivity of the substrate when maintained at a floating potential, increasing with the permittivity of the plate [4]. Regarding the works published by other groups, the interaction of a kHz sinusoidal Ar APPJ with different metal plates (at floating potential) resulted in a noticeable increase of the intensities of the emission spectra of the APPJ [26]. On top of that, it was found that an rf-driven Ar APPJ does not penetrate into a thin capillary tube (inner diameter=250 μm) when the tube is maintained at a floating potential; but the placement of a grounded metallic ring downstream of the capillary orifice allows for the jet to penetrate inside the tube [24].…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Besides, we also reported that the absolute density of Ar(1s5) metastables depends on the permittivity of the substrate when maintained at a floating potential, increasing with the permittivity of the plate [4]. Regarding the works published by other groups, the interaction of a kHz sinusoidal Ar APPJ with different metal plates (at floating potential) resulted in a noticeable increase of the intensities of the emission spectra of the APPJ [26]. On top of that, it was found that an rf-driven Ar APPJ does not penetrate into a thin capillary tube (inner diameter=250 μm) when the tube is maintained at a floating potential; but the placement of a grounded metallic ring downstream of the capillary orifice allows for the jet to penetrate inside the tube [24].…”
Section: Introductionmentioning
confidence: 63%
“…For Ar APPJs, numerous works can be found referring mostly to the surface modification of polymeric materials [19][20][21][22]. Contrary to He jets, fewer studies focusing on the dynamics of Ar APPJs impinging on substrates have been published so far [2,4,13,[23][24][25][26][27]. Among them, the improvement of the stability of a ns-pulsed APPJ when impinging on a floating-potential glass plate was reported lately by our group [2,27].…”
Section: Introductionmentioning
confidence: 99%